N-hydroxypipecolic acid primes plants for enhanced microbial pattern-induced responses - Löwe, Marie; Jürgens, Katharina; Zeier, Tatyana; Hartmann, Michael; Gruner, Katrin; Müller, Sylvia; Yildiz, Ipek; Perrar, Mona; Zeier, Jürgen (Frontiers in Plant Science, 2023)
The bacterial elicitor flagellin induces a battery of immune responses in plants. However, the rates and intensities by which metabolically-related defenses develop upon flagellin-sensing are comparatively moderate. We report here that the systemic acquired resistance (SAR) inducer N hydroxypipecolic acid (NHP) primes Arabidopsis thaliana plants for strongly enhanced metabolic and transcriptional responses to treatment by flg22, an elicitor-active peptide fragment of flagellin. While NHP powerfully activated priming of the flg22-induced accumulation of the phytoalexin camalexin, biosynthesis of the stress hormone salicylic acid (SA), generation of the NHP biosynthetic precursor pipecolic acid (Pip), and accumulation of the stress-inducible lipids -tocopherol and stigmasterol, it more modestly primed for the flg22-triggered generation of aromatic and branched-chain amino acids, and expression of FLG22-INDUCED RECEPTOR-KINASE1. The characterization of the biochemical and immune phenotypes of a set of different Arabidopsis single and double mutants impaired in NHP and/or SA biosynthesis indicates that, during earlier phases of the basal immune response of naïve plants to Pseudomonas syringae infection, NHP and SA mutually promote their biosynthesis and additively enhance camalexin formation, while SA prevents extraordinarily high NHP levels in later interaction periods. Moreover, SA and NHP additively contribute to Arabidopsis basal immunity to bacterial and oomycete infection, as well as to the flagellin-induced acquired resistance response that is locally observed in plant tissue exposed to exogenous flg22. Our data reveal mechanistic similarities and differences between the activation modes of flagellin-triggered acquired resistance in local tissue and the SAR state that is systemically induced in plants upon pathogen attack. They also corroborate that the NHP precursor Pip has no independent immune-related activity.